IMPACT OF COLOUR SYMBOLISM ON ENGLISH COLOUR IDIOMS AND THEIR GEORGIAN EQUIVALENTS - Nino Kemertelidze; Meri Giorgadze (International Journal of Innovative Technologies in Social Science, 2021)
The presented article aims to study colour idioms; to be more precise, idioms one element of which is a colour designating word. During the research, we were interested in identifying whether the symbolic loading of certain colours has an impact on the meaning of an idiom. The conducted research revealed that colour symbolism greatly influences the meaning of colour idioms in the English language. More specifically, it conditions the implication of the whole idiomatic phrase. While conducting the research, we studied about 200 colour idioms in the English language and tried to find out their Georgian equivalents. It appeared that 94 idioms did not have the corresponding Georgian versions on the etic level. Consequently, 106 ones had the corresponding Georgian translations, out of which 30 phrases were transferred into the Georgian language as idiomatic expressions and colour was maintained only in 17 of them. Besides, it is noteworthy that one and the same colour can have different symbolic loadings what is vividly seen in the presented work.